Design Comparison of an RC Retaining Wall with BS8110 and EC 2 - Tan, Aloysius Sze Howe (2015)
The purpose of this project is to design a cantilever retaining wall using l3S1 10 and EC2 and do a comparison between them. Retaining wall is the more efficient, safe and space-saving structure than the traditional method. There are a lot of different designs of retaining walls but in this project, cantilever retaining wall is chosen because of its advantages than other designs. There are a lot of differences between British Standards and Eurocode, and some of it will be applied ¡n this project. The calculation differences will be tabulated out at the end of the project. Calculation will be on firstly, the stability of the wall: and second the reinforcement. The different codes have different formulae and will produce various results.